Risk Factors of Antituberculosis Induced-Hepatotoxicity among HIV/AIDS Patients - Lies Luthariana; Teguh H. Karjadi; Irsan Hasan; C. Martin Rumende (Jurnal Penyakit Dalam Indonesia)
Introduction. Antituberculosis (ATT) induced hepatotoxicity is commonly found among HIV/AIDS patients. Several risk factor related to drug-induced hepatotoxicity such as alcoholism, hepatitis B or hepatitis C infection, abnormal baseline aminotransferase/bilirubin, poor nutritional status and concomitant hepatotoxic drugs consumption, are usually found in these patients. This study was conducted to evaluate risk factor of ATT-induced hepatotoxicity in HIV/AIDS patients. Methods. This is a case control retrospective study with matching of age, sex, antituberculosis regimen, and alcohol consumption. Risk factors evaluated are hepatitis C and hepatitis B coinfection, concomitant hepatotoxic drugs consumption, abnormal baseline aminotransferase and or bilirubin.